THE IMPACT OF ORGANIZATIONAL CULTURE AND TRANSFORMATIONAL LEADERSHIP STYLE ON WORK MOTIVATION TO ENHANCE EMPLOYEE PERFORMANCE AT PT KWARSA INDAH MURNI - Rusli Hardjadinata; Ginta Ginting; Ratno Purnomo (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Employee performance is crucial to the company's ability to survive in the economic climate of tshe COVID-19 pandemic. This motivates PT Kwarsa Indah Murni's Glass Table Ware Industry to continue to enhance its performance. The purpose of this analysis is to gain a deeper understanding of how organizational culture and a transformational leadership style can inspire the 380 employees of PT Kwarsa Indah Murni to give their best work. Researchers used quantitative descriptive statistics. The study population was 380 employees of the PT Kwarsa Indah Murni. For data obtained using a questionnaire. In this analysis, 100 respondents took part, and 80 datasets totaled and eligible for analysis. The data was analyzed utilizing the Smart 3.0 Partial Least Squares (PLS) model. According to the analysis's results, organizational culture has an effect on employee motivation. Motivation at work is unaffected by a transformational leadership style. Employee performance is impacted by work motivation. Organizational culture has an impact on employee performance. Transformational leadership has an impact on employee performance as well